Decolonizing Central Europe: Czech Art and the Question of 'Colonial Innocence'. (2nd January 2021) - Rampley, Matthew
Abstract : The recent call to decolonize art history and the institutions of art have largely focused on the legacies of the major European and American colonial powers, such as Britain, France, Spain and the United States. Positioning Europe at the heart of modernity/coloniality prompts questions to do with how to place the states and cultures of east central Europe, none of which had colonial territories or engaged in projects of expropriation and colonial exploitation. It was along assumed that states such as Poland, Hungary and the Czech Republic were little touched by the debate over decolonization, precisely because they had no overseas colonial empires. Belief in 'colonial innocence' was an important aspect of national self-definition. This article examines this conviction with reference to the specific case of the Czech lands and Czechoslovakia. Looking at practices of cultural representation, museum collecting and architecture in the nineteenth and early twentieth centuries, it suggests that the idea of colonial innocence is open to interrogation.